1991
DOI: 10.1182/blood.v77.1.133.133
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against CD4 cells are associated with CD4 helper defects in human immunodeficiency virus-infected patients

Abstract: To investigate whether autoantibodies against CD4-positive lymphocytes might induce helper dysfunction, autoantibody formation and T-cell function was examined simultaneously in 61 hemophilia patients. Twenty patients were human immunodeficiency virus (HIV)-negative, 26 HIV- positive stage CDC II or III, and 15 were HIV-positive stage CDC IV. T lymphocytes, CD4-positive, or CD8-positive T subsets were cocultured with B lymphocytes and pokeweed mitogen (PWM) for 6 days and Ig- secreting cells were assessed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Interestingly, CD8 + lymphocytes decrease in association with the immune complex load of CD4 + lymphocytes ( Table 1). The decreased helper cell function of CD4 + lymphocytes for CD8 + cells seems to have an overall suppressive effect on CD8 + cells, similar to that noted previously for B lymphocytes [12]. The impaired helper function of CD4 + lymphocytes thus appears to reduce the proliferation of anti-viral CD8 + lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, CD8 + lymphocytes decrease in association with the immune complex load of CD4 + lymphocytes ( Table 1). The decreased helper cell function of CD4 + lymphocytes for CD8 + cells seems to have an overall suppressive effect on CD8 + cells, similar to that noted previously for B lymphocytes [12]. The impaired helper function of CD4 + lymphocytes thus appears to reduce the proliferation of anti-viral CD8 + lymphocytes.…”
Section: Discussionsupporting
confidence: 80%
“…HIV infection is characterized by a progressive dysfunction and depletion of CD4 + lymphocytes [1]. During the course of HIV disease autoantibodies against CD4 + lymphocytes are formed and gp120-IgG/IgM-complement complexes are detectable on circulating CD4 + lymphocytes during late stages of the disease [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, we reported that gp120-containing immune complexes on CD4 + lymphocytes are associated with both dysfunction and depletion of CD4 + blood lymphocytes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Cell separations were performed as described previously [22][23][24]. Briefly, PBMC were separated into 'whole' T and non-T cells (termed B cells in the following) by the rosetting technique.…”
Section: Cell Culturesmentioning
confidence: 99%
“…the production of autoantibodies in human immunodeficiency virus (HIV) infection. In HIV-infected patients, a large spectrum of autoantibodies is found, reflecting a specific stimulation of B cells (Weimer et al 1991, Susal et al 1992, Kouri et al 1992, Ditzel et al 1994. It has been demonstrated that the outer envelope glycoprotein of HIV-l gpl20 behaves as a B-cell superantigen, since it binds to 4-6% of B cells belonging to the VH3 family (Berberian et al 1993).…”
Section: B-cell Mitogentc Virus Involved In Breaking Of Tolerance 69mentioning
confidence: 99%